The antitumor efficacy of cisplatin in combination with triptorelin and exemestane therapy for an ovarian cancer ascites model in Wistar rats - Tkalia, I.G.; Vorobyova, L.I.; Grabovoy, A.N.; Svintsitsky, V.S.; Tarasova, T.О. (Experimental Oncology, 2015)
Aim: To study antitumor activity of triptorelin — agonist of gonadotropin-releasing hormone and exemestane — inhibitor of aromatase in combination with cisplatin on the model of receptor-positive for estrogens and progesterone malignant transplantable ascites ovarian tumor (OT); to assess tumor response to treatment and VEGF expression in tumor cells under different combinations of cytostatic and hormonal drugs. Materials and Methods: 36 female Wistar rats, which underwent intraperitoneal transplantation of ascites OT (5×106 cells per animal), have been involved in the study. Rats were distributed into 4 groups (9 rats in each group): group 1 — animals, which received combination of cisplatin and triptorelin; group 2 — rats treated with combination of cisplatin and exemestane; group 3 — animals, which were administered with combination of cisplatin, triptorelin and exemestane; group 4 — rats, which received combination of triptorelin and exemestane. Histological study with assessment of treatment pathomorphosis in OT and immunohistochemical study have been carried out to analyze VEGF expression in OT cells. Survival of animals has been evaluated. Results: Combination of cytostatic agent with triptorelin or exemestane has demonstrated significantly higher rates of treatment pathomorphosis (10.1 ± 0.1% and 16.2 ± 0.3%, respectively) and antiangiogenic activity in OT (21.4 ± 1.4% and 15.0 ± 1.3%, respectively), as well as the highest survival of animals (100.0 and 85.7%, respectively) as compared with the same in rats treated in regimen of monotherapy with cisplatin, triptorelin, exemestane or by combination of hormonal drugs. Among animals treated by combination of cytostatic drug with triptorelin, two were cured (22.2%), and among rats, which received cisplatin and exemestane, one animal (11.1%) was cured. Conclusions: Triptorelin and exemestane increase antitumor activity of cisplatin in respect to the transplantable malignant ascites OT and significantly increase survival of animals, especially when triptorelin and cisplatin are used in combination. Key Words: transplantable ascites ovarian tumor, rat, cisplatin, agonist of gonadotropin-releasing hormone triptorelin, inhibitor of aromatase exemestane, treatment pathomorphosis, VEGF, survival.